2021
DOI: 10.1038/s41522-020-00176-2
|View full text |Cite
|
Sign up to set email alerts
|

Host development overwhelms environmental dispersal in governing the ecological succession of zebrafish gut microbiota

Abstract: Clarifying mechanisms underlying the ecological succession of gut microbiota is a central theme of gut ecology. Under experimental manipulations of zebrafish hatching and rearing environments, we test our core hypothesis that the host development will overwhelm environmental dispersal in governing fish gut microbial community succession due to host genetics, immunology, and gut nutrient niches. We find that zebrafish developmental stage substantially explains the gut microbial community succession, whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 72 publications
(126 reference statements)
5
72
0
Order By: Relevance
“…This is consistent with Hayes et al (2020) 41 , where the authors showed neutral processes dominated the gut microbiome in farmed Atlantic salmon ( Salmo salar ). In contrast, however, other authors have found a decreasing influence of neutral processes over time in zebrafish ( Danio rerio ) gut microbial communities 42,43 . However, environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This is consistent with Hayes et al (2020) 41 , where the authors showed neutral processes dominated the gut microbiome in farmed Atlantic salmon ( Salmo salar ). In contrast, however, other authors have found a decreasing influence of neutral processes over time in zebrafish ( Danio rerio ) gut microbial communities 42,43 . However, environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 79%
“…This may point to host-associated factors, however, it is difficult to say with certainty in our study design if patterns are due to host-associated pressures. Host development was found to be a significant influence on driving deterministic microbial community assembly in the zebrafish gut 42 . However, host pressures in the juvenile or adult cod gut are not widely described, a study design similar to the zebrafish study but with Atlantic cod could help elucidate these factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, to maintain its basic intestinal functionality, the host also actively selects for symbiotic and commensal microorganisms. Therefore, the gut microbiota is influenced by both external factors and the selective pressure exerted by the host [23][24][25][26]. Compared to the surrounding environment, the microbial communities associated with an organism are regarded as relatively stable, particularly those in the GIT [27,28], which assures metabolic, nutritional, and immunologic functionality.…”
Section: The "Living Gut" and Its Core Microbiomementioning
confidence: 99%
“…However, it seems that the gut microbiota of larval shrimp is more similar with the rearing bacterioplankton community, compared with the adults (Burns et al, 2016;Xiong et al, 2018). A possible explanation is that the selection on external taxa is increased as host matured (Xiong et al, 2019a;Xiao et al, 2021). However, the deteriorated water quality imposes stress on shrimp, which in turn depresses their capability of filtering on external taxa (Xiong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there is non-linear trend in the relative importance of deterministicity in governing the gut microbiota over shrimp development (Xiong et al, 2019b). It is now recognized that the gut microbiota is conjointly affected by rearing geochemical variables, bacterioplankton, and host development (Xiong et al, 2019b;Xiao et al, 2021), while little is known on the interplay among these variables. Theoretical evidence has proposed that the successional pattern of host-associated (e.g., gut microbiota) communities is distinct from that of free-living bacteria (e.g., bacterioplankton) (Baselga, 2010;Xiong et al, 2019b), whereas experimental evidence is lacking.…”
Section: Introductionmentioning
confidence: 99%